2001
DOI: 10.1007/bf02479423
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors such as sodium butyrate and trichostatin A induce apoptosis through an increase of the bcl-2-related protein Bad

Abstract: The effects of sodium butyrate (SB) and trichostatin A (TSA) on cell proliferation andapoptosis against human glioma T98G, U251MG, and U877MG cells were investigated. Upon exposure to either SB or TSA, cell proliferation was reduced, and apoptosis detected by DNA fragmentation analysis and the cleavage of CPP32 was induced. Previously, we reported that SB increased the expression levels of p21 (WAF-1) and inhibited G1-S transition of the cell cycle. In this study, we showed that TSA also increased p21 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 17 publications
3
45
0
Order By: Relevance
“…For example, in hepatoma and breast cancer cells, HDAC inhibition decreased the expression of Bcl-2, while expression of pro-apoptotic Bax was increased [33,44] , in line with the present study. On the other hand, no changes in the expression pattern of Bax and Bcl-2 were found in HDAC-inhibitor-treated glioma cells [45] , and in gastrointestinal neuroendocrine tumor cells, Bcl-2 expression was down-regulated upon MS-275 treatment, while Bax remained unchanged [24] . Especially for an estimation of suitable combination treatment regimens being based on the enhanced induction of apoptosis, it is necessary to check out cell type-specific changes in the expression pattern of HDAC-induced pro-and antiapoptotic proteins.…”
Section: Discussionmentioning
confidence: 88%
“…For example, in hepatoma and breast cancer cells, HDAC inhibition decreased the expression of Bcl-2, while expression of pro-apoptotic Bax was increased [33,44] , in line with the present study. On the other hand, no changes in the expression pattern of Bax and Bcl-2 were found in HDAC-inhibitor-treated glioma cells [45] , and in gastrointestinal neuroendocrine tumor cells, Bcl-2 expression was down-regulated upon MS-275 treatment, while Bax remained unchanged [24] . Especially for an estimation of suitable combination treatment regimens being based on the enhanced induction of apoptosis, it is necessary to check out cell type-specific changes in the expression pattern of HDAC-induced pro-and antiapoptotic proteins.…”
Section: Discussionmentioning
confidence: 88%
“…Differences in the expression pattern of apoptosisrelated proteins seems to be cell-type dependent. For example, in hepatoma cells, TSA decreased the expression of Bcl-2, while expression of proapoptotic Bax was increased (Herold et al 2002), no change of Bax and Bcl-2 expression was found in glioma cells with either TSA or NaB treatment (Sawa et al 2001). MS-275 has been described to downregulate Bcl-2 and upregulate Bax expression in breast cancer cells (Singh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical potential of these agents has been documented by several Phase I trials of different HDIs in patients with solid tumors or leukemias (12)(13)(14)(15)(16)(17). Various HDIs have been evaluated in brain tumors in a few studies (18)(19)(20)(21)(22) but, with the exception of MS-275 (23) and phenylbutyrate and phenylacetate (24), not in pediatric medulloblastoma.…”
Section: Introductionmentioning
confidence: 99%